SOME FACTORS AFFECTING WORK MOTIVATION IN IMPROVING WORK PRODUCTIVITY OF EMPLOYEES IN PT. DWITUNGGAL ABADI PERMAI JAKARTA UTARA - Darmawan, Sukaria (Jurnal Manajemen, 2019)
This study examines the factors that influence work motivation towards increasing employee work productivity at PT. Dwitunggal Abadi Permai North Jakarta. The purpose of this research is to find out the factors that influence work motivation towards increasing employee work productivity at PT. Dwitunggal Abadi Permai North Jakarta. In increasing employee work productivity, a company needs to plan a strategy and create good and professional management. For that production is the center of the implementation of concrete activities for the procurement of goods and services in a business entity and company. The production process is the most important part of the company, because if it stops, the company will suffer losses. In production activities the labor factor (employee) has a large influence, because the workforce is the one who carries out the production process. For this purpose, all of the resources in the agency must be utilized as well as possible, including human resources as the main factor. Human resources needed today are those who have a leadership style that is good for performance, potential and good loyalty to the agency. So that the employees are able to describe the vision and mission that have been agreed upon together in order to achieve agency goals. This research was conducted at the Basarnas office in South Sumatra. In the results of R square (R2) Obtained a value of 0.013 means the percentage of the contribution of leadership style to employee performance 1.3% while the remaining 98.7% is influenced by other variables not included in this model. on the leadership style variable (X) the value of t is equal to 1-195 while the value of t table is 1.645 because t count (-1.945 because t count (-1.945)> t table (1,645), based on hypothesis testing that leadership style is very influential on performance employee.